Pengaruh Product Quality Dan Product Innovation Terhadap Purchase Decisions (Studi Kasus Pada Pelanggan Starbucks Kec. Klojen, Kota Malang) - Nanda Rifky V. A; N. Rachma; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of product quality and product innovation on purchase decisions through partial or simultaneous. This research is a type of explanatory research. The population of this research is the customers from Starbucks located in Kec. Klojen, Malang City. The sampling technique used in this research was purposive sampling technique consisting of 75 respondents with predetermined criteria. This study uses quantitative methods, data collection uses a questionnaire method with a Likert scale as a measuring tool for respondents answers. Data analysis used multiple linear regression analysis. The results of this study indicate that product quality and product innovation has a positive and significant effect on purchase decisions. Keywords: Product Quality, Product Innovation, Purchase Decisions